FBXW8 regulates G1 and S phases of cell cycle progression by restricting β‐TrCP1 function. (5th April 2021) - Islam, Sehbanul; Dutta, Parul; Chopra, Kriti; Rapole, Srikanth; Chauhan, Radha; Santra, Manas Kumar
Abstract : Sequential alteration in the expression levels of cell cycle regulatory proteins is crucial for faithful cell cycle progression to maintain the cellular homeostasis. F‐box protein β‐TrCP1 is known to control the expression levels of several important cell cycle regulatory proteins. However, how the function of β‐TrCP1 is regulated in spatiotemporal manner during cell cycle progression remains elusive. Here, we show that expression levels of β‐TrCP1 oscillate during cell cycle progression with a minimum level at the G1 and S phases of cell cycle. Using biochemical, flow cytometry, and immunofluorescence techniques, we found that oscillation of β‐TrCP1 expression is controlled by another F‐box protein FBXW8. FBXW8 directs the proteasomal degradation of β‐TrCP1 in MAPK pathway‐dependent manner. Interestingly, we found that the attenuation of β‐TrCP1 by FBXW8 is important for Cdc25A‐mediated cell cycle transition from G1 phase to S phase as well as DNA damage‐free progression of S phase. Overall, our study reveals the intriguing molecular mechanism and significance of maintenance of β‐TrCP1 levels during cell cycle progression by FBXW8‐mediated proteasomal degradation. Abstract : F‐box protein β‐TrCP1 plays vital role in cell cycle progression through controlling expression levels of many cell cycle regulatory proteins. However, its own regulation during cell cycle progression was poorly understood. Here, we showed that F‐box protein FBXW8 restricts the cellular function of β‐TrCP1 in MAPK pathway‐dependent manner to monitor G1 to S phase transition as well as S phase progression.